2020
DOI: 10.1088/1757-899x/935/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

A review of sustainable replanting eucalyptus: higher sustainable productivity

Abstract: Eucalyptus is a plant that has a very beneficial value to the environment such as can reduce the risk of forest fires, be efficient in water use, nature became more natural, restore land degradation or unproductive land, and the growth of these plants has a sustainable potential for biodiversity. Therefore, the need to replant eucalyptus in order to create a sustainable process for the environment to offers opportunities for wealth and prosperity, while also providing solutions for efficient ways to combat cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The eucalyptus plant IOP Publishing doi:10.1088/1742-6596/2421/1/012009 7 has been cultivated by more than 90 countries in the world. So that the impact of increasing productivity has the opportunity to cover globally [20].…”
Section: Economic Dimensionmentioning
confidence: 99%
“…The eucalyptus plant IOP Publishing doi:10.1088/1742-6596/2421/1/012009 7 has been cultivated by more than 90 countries in the world. So that the impact of increasing productivity has the opportunity to cover globally [20].…”
Section: Economic Dimensionmentioning
confidence: 99%
“…Long-term studies have demonstrated that the eucalyptus plantations are sustainable, and very efficient at capturing CO 2 (240 tons of CO 2 per ha over a 7-year rotation (IBÁ 2022). Furthermore, under the norms of the Brazilian Forest Code, landowners may only establish plantations on degraded land and must commit between 20% and 50% of their land to native forest renewal, making this industry one of the global leaders in degraded land restoration (Grossberg 2009;Sembiring et al 2020;Coelho et al 2022).…”
Section: Fixing the Supply-demand Gap By 2050-increasing The Producti...mentioning
confidence: 99%
“…Eucalyptus is very adaptable, tolerating low soil fertility, acidic soils, and soils rich in aluminium, often periodic moisture stress, diverse climates and soil types, and even fire and insect damages and low water availability [11][12][13][14][15]. Other favourable characteristics of Eucalyptus include its good efficiency at capturing CO 2 and producing oxygen, better efficiency in water consumption compared to other species, increasing soil fertility, and restoring land degradation or unproductive land [16,17].According to Myburg [18] and Iglesias Trabado and Wilstermann [19], currently there are more than 100 countries across six continents around the world planting Eucalyptus and covering over 20 million ha, making it the most widely planted broad-leaved tree species worldwide. From 1990 to 2015, the global Eucalyptus plantation area increased by 16.57 million ha, with an average annual increase of 1.1 million ha.…”
Section: Introductionmentioning
confidence: 99%